Antioxidant Activity Test of Ethanol Extract of Kesum Leaves (Polygonum Minus Huds) Using the DPPH Method - Qori Hasanah Hasibuan; Nerly Juli Pranita Simanjuntak; Roy Indriyanto Bangar (Sean Institute, 2026)
Kesum leaves (Polygonum minus Huds.) are herbal plants with potential as natural sources of antioxidants. This study aimed to evaluate the antioxidant activity of the ethanol extract of kesum leaves using the DPPH method and to identify the types of secondary metabolites present. Extraction was performed by maceration using 70% ethanol. Phytochemical screening was conducted qualitatively, while antioxidant activity was determined based on IC₅₀ values measured using a UV–Vis spectrophotometer at a wavelength of 517 nm, with vitamin C used as a reference standard. The results showed that the ethanol extract of kesum leaves contained alkaloids, flavonoids, tannins, triterpenoids, and steroids. The antioxidant activity test revealed that the ethanol extract had an IC₅₀ value of 7.9241 µg/mL, which was classified as having very strong antioxidant activity. In comparison, vitamin C exhibited a lower IC₅₀ value of 3.2886 µg/mL, indicating stronger antioxidant activity. These findings indicate that although the antioxidant activity of the ethanol extract of kesum leaves is lower than that of vitamin C, the extract still falls into the category of very strong antioxidants and has potential as a natural antioxidant source.